Behavior under social pressure: empty Italian stadiums and referee bias - Per Pettersson-Lidbom; Mikael Priks (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper studies how social pressure affects the behavior of soccer referees. We make use of an attractive source of exogenous variation in the number of spectators at matches. Due to recent hooligan violence, the Italian government has implemented a regulation that forces some soccer teams to temporarily play home matches in empty stadiums. We find that referees punish away players more harshly and home players more lightly when the games are played in front of spectators compared to when they are not. This indicates that referees exhibit home bias caused by social pressure from the spectators.
Keywords: J00; 330; Schiedsgerichtsbarkeit; Soziale Beziehungen; Fußballsport; Verhalten; Italien